Impact of The Covid-19 Pandemic on Financial Performance of Logistics and Delivery Companies Listed on ISSI - Muhamad Rizal Kurnia; Syihabudin Syihabudin; Najmudin Najmudin (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
The limited activities outside the home due to the Covid-19 pandemic have made people spend more online shopping. The rapid development of e-commerce and online shopping has become a huge opportunity in the logistics and delivery (courier) sector because it is one of the essential industries that is allowed to continue operating and a sector that plays a vital role in supporting the community's economy during the Covid-19 pandemic. This study aims to determine the impact of the Covid-19 pandemic on the financial performance of logistics and shipping companies listed on the Indonesian Sharia Stock Index (ISSI). This research method uses descriptive quantitative using financial ratio calculations to describe the company's financial performance which is used is ROA, NPM, and DER. The data source is secondary data for the 2019-2021 quarterly financial statements at PT Satria Antaran Prima Tbk and PT Trimuda Nuansa Citra Tbk. obtained from the idx.co.id website page. The results of this study indicate that before the 2019 Covid-19 pandemic, the company's financial performance on ROA and NPM increased and DER tended to decrease. During the Covid-19 pandemic in 2020-2021 ROA and NPM decreased and DER increased. Company's financial performance logistics and delivery shows that before Covid-19 was better than during the Covid-19 pandemic